The Treasure of the Lexicon of Kepadian in the Bugis Society: An Ecolinguistic Study - Supriadi Supriadi; Nurjayanti Kaharuddin (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research aims to explain (1) the form and category of the compact lexicon in the Bugis society; (2) Cultural value or meaning in the myth speech of the kepadian bugis society. The data collection method used in research is a method of observation, which is carefully the speech expressed by informants, especially speech related to the data lexicon of cohesion. This method is accompanied by several techniques such as the technique of listening to observation- participatory, interviews, audiovisual recording, and taking notes. Data is quantitatively analyzed. The results showed that there are various forms and categories of compact lexicon in the Bugis society. Treasures of the compact lexicon in the Bugis society that patronize the lexicon dynamics of cohesion in the Bugis society, changes in the physical and social environment; the development of science and technology; Changes in the mental attitudes of the younger generation towards the values, norms, and socio-cultural prevailing in society. Keywords: Kepadian lexicon, Bugis culture, ekolinguistic Abstrak Penelitian ini bertujuan menjelaskan (1) bentuk dan kategori leksikon kepadian pada masyarakat Bugis; (2) nilai budaya atau makna dalam tuturan mitos kepadian masyarakat Bugis. Metode pengumpulan data yang digunakan dalam penelitian adalah metode simak (pengamatan), yaitu secara seksama tuturan yang diujarkan oleh informan, terutama tuturan yang berkaitan dengan data leksikon kepadian. Metode ini disertai dengan beberapa teknik seperti teknik simak libat cakap (observasi- partisipatuf), wawancara, rekam secara audiovisual, dan catat. Data dianalisis secara kuantitatif. Hasil penelitian menunjukkan bahwa terdapat bermacam-macam bentuk dan kategori leksikon kepadian pada masyarakat Bugis. Khazanah leksikon kepadian pada masyarakat Bugis yang memenguruhi dinamika leksikon kepadian pada masyarakat Bugis, yakni terjadi perubahan lingkungan fisik dan sosial; perkembangan ilmu pengetahuan dan teknologi; perubahan sikap mental generasi muda terhadap nilai, norma, dan sosio kultural yang berlaku dalam masyarakat. Kata kunci: leksikon Kepadian, budaya Bugis, ekolinguistik